Violencia de pareja desde la perspectiva del hombre maltratado - Jaya Valdiviezo, Paola Madelaine; Veloz Landázuri, Cynthia Elizabeth (Machala: Universidad Técnica de Machala, 2020)
Partner violence is part of the modality of interpersonal violence that arises within the family between two people who are emotionally related without their marital or cohabitation status prevailing, where a member acts as an aggressor exercising on the victim an active behavior, of action or omission with the intention of hurting, damaging or controlling, manifesting according to its typology as physical, psychological, economic, social or sexual violence, causing psychological affectations at the emotional, cognitive and behavioral level in the abused person . In general, when emphasizing partner violence, it is thought that only the woman is a victim, however, the man does not always act as an aggressor and currently the cases of male victims of abuse have increased, that is why the interest has arisen to gather information from that, being the present investigation that aims to identify, the psychological effects that prevail in battered men whose factors affect the choice to continue with their romantic partner with violent behavior, through the analysis of the influential family context. The research was carried out under the modality of mixed, qualitative-quantitative study, with descriptive and interpretative scope and the methods used were analytical-synthetic, narrative-biographical. The approach used was the Systemic, understood as the study of the parts and of the whole, which are composed and interconnected in a certain context by relations between the subsystems and nearby external systems that influence others, therefore, it was taken as the basis epistemological and support theory the Systemic Ecological Model. The categories of analysis were partner violence regarding their modalities, psychological affectations and psychosocial factors that influence battered men to continue with their partner. The three study subjects are adults between 26 and 35 years old, live with their partners and children and have been victims of violence in the last six months. The techniques applied were, semi-structured interview of the participants and to complement the data obtained by the reagents: Domestic Violence: Frequency and Perception VIDOFyP identifies the type of violence, Questionnaire of Emotional Response to Violence REV assesses 4 dimensions depression, anxiety, psychosocial adjustment and irritable mood, Beck Depression Inventory BDI-II assesses depressive symptomatology, The Hamilton Anxiety Assessment Scale HAM-A assesses psychic and somatic anxiety from absence to its maximum intensity, and Scale of Flight Blocking in Situations of Abuse EBHSM identifies the factors for a person to remain in a situation of violence. It is concluded that in the cases studied physical and psychological violence was evidenced including economic and social violence, mixed symptoms of depression and anxiety that influence the areas of their daily lives, while the impact that the separation of the couple has on the children, beliefs regarding the hope that the couple modifies their abusive attitudes, ambivalent anxious attachment style and emotional dependence on the couple, are psychosocial factors that motivate the subjects Continue with your partners.
La violencia de pareja es parte de la modalidad de la violencia interpersonal que surge al interior del seno familiar entre dos personas que se encuentran relacionadas de forma afectiva sin que prevalezca su estado civil o de convivencia, donde un miembro actúa como agresor ejerciendo sobre la víctima una conducta activa, de acción u omisión con la intención de herir, dañar o controlar, manifestándose de acuerdo a su tipología como violencia física, psicológica, económica, social o sexual, provocando afectaciones psicológicas a nivel emocional, cognitivo y comportamental en la persona maltratada. Por lo general cuando se enfatiza en la violencia de pareja se piensa que solamente la mujer es víctima, sin embargo, el hombre no siempre actúa como agresor y actualmente los casos de hombres víctimas de maltratos se han acrecentado, es por eso que ha surgido el interés de recabar información de aquello, siendo la presente investigación que tiene como objetivo identificar las afectaciones psicológicas que prevalecen en hombres maltratados cuyos factores inciden en la elección de continuar con su pareja sentimental con comportamientos violentos, por medio del análisis del contexto familiar influyente. La investigación se realizó bajo la modalidad de estudio mixto, cualitativo- cuantitativo, con alcance descriptivo e interpretativo y los métodos usados fueron el analítico-sintético, narrativo–biográfico. El enfoque empleado fue el Sistémico, comprendido como el estudio de las partes y del todo, que se encuentran compuestos e interconectados en un determinado contexto por relaciones entre los subsistemas y sistemas externos próximos que influyen en los demás, por ende, se tomó como base epistemológica y teoría de soporte el Modelo Ecológico Sistémico. Las categorías de análisis fueron la violencia de pareja referente a sus modalidades, afectaciones psicológicas y los factores psicosociales que influyen a que los hombres maltratados continúen con su pareja. Los tres sujetos de estudio son adultos entre los 26 a 35 años, conviven con sus parejas e hijos y han sido víctimas de violencia en los últimos seis meses. Las técnicas aplicadas fueron: entrevista semiestructurada a los participantes y para complementar los datos obtenidos los reactivos: Violencia Doméstica: Frecuencia y Percepción VIDOFyP identifica la tipología de violencia, Cuestionario de Respuesta Emocional a la Violencia REV valora 4 dimensiones (depresión, ansiedad, ajuste psicosocial y humor irritable), Inventario de Depresión de Beck BDI-II valora sintomatología depresiva, La Escala de Evaluación de la Ansiedad de Hamilton HAM-A valora ansiedad psíquica y somática desde la ausencia hasta su intensidad máxima, y Escala de Bloqueo de la Huida en Situaciones de Maltrato EBHSM identifica los factores para que una persona permanezca en una situación de violencia. Se concluye que en los casos estudiados se evidenció violencia física y psicológica incluyendo la violencia económica y social, sintomatología mixta de depresión y ansiedad que influyen en las áreas de su vida cotidiana; mientras que el impacto que tenga la separación de la pareja en los hijos, creencias respecto a la esperanza de que la pareja modifique sus actitudes maltratantes, estilo de apego ansioso ambivalente y dependencia emocional hacia la pareja, son factores psicosociales que motivan a que los sujetos continúen con sus parejas.
Keywords: VIOLENCIA DE PAREJA; HOMBRE MALTRATADO; AFECTACION; PSICOSOCIAL